GRAVITY-ANOMALIES, CRUSTAL STRUCTURE AND FLEXURE OF THE LITHOSPHERE AT THE BALTIMORE CANYON TROUGH - Watts, A (1988)
Seismic and gravity anomaly data have been used to examine the long-term mechanical properties of the lithosphere beneath the Baltimore Canyon Trough, a 15 km deep sedimentary basin in the rifted U.S. Atlantic margin. Seismic data constrain the crustal structure at the time of rifting as well as the amount of sedimentation and erosion that has occurred. The gravity effect of the initial crustal structure, sedimentary loading and erosional unloading have been computed and compared to the observed free-air gravity anomaly. The best fitting model is one in which the elastic thickness of the lithosphere (Te) changes at the East Coast magnetic anomaly. Landward of the anomaly, Te is significantly smaller than previously reported values for continental or oceanic lithosphere of the same thermal age. Seaward of the anomaly, however, Te follows the depth to the 450°C oceanic isotherm which also describes the response of oceanic lithosphere to seamount and oceanic island loads. These results are interpreted as indicating that the shelf part of the trough is underlain by continental lithosphere which, following rifting, did not acquire any significant long-term strength. © 1988.